Demographic profile and pathway to care in patients with schizophrenia in a tertiary care hospital from western Nepal (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: Schizophrenia is one of the severe mental health problem and its guarded treatment response and association with as the stigma makes it a chronic debilitating personal, family and social problem of all the psychiatric illness. Timely Identification and management of this condition is important as early diagnosis and management gives better treatment response.Methods: This is a descriptive study done in patients attending psychiatry OPD of Nepalgunj Medical College, Kohalpur for 12 months from June 2013 to May 2014.Results: Out of the 86 study subjects (n=86), males were 54 in number followed by 32 females. The most common age group was 21-40 years representing 46(53.4%), followed by 41-60 years 24(28%), 60 years 4(4.7%). The most common first contact of the patient with schizophrenia was with faith healers 54 (62.8%) followed by consultation with psychiatrist 18(20.9%). Among the study population, 38(44.2%) visited to the psychiatrist after >41 weeks of the beginning of the illness followed by 34(39.5%) visited in